STUDENTS' LEARNING EXPERIENCE ON THE IMPLEMENTATION OF 'STARLIGHT CADRE' ACTIVITY ON STUDENTS' SPEAKING SKILL AT SMAN 1 TUNTANG - Trista Ayu Farasya; Alfina Eka Ri’ayatul K.; Nadia Himmatul Aliyyah; Mashlihatul Umami; Agus Setiyono (LPPM Universitas PGRI Jombang, 2025)
This research aims to examine the implementation and effectiveness of the Starlight Cadre activity to improve speaking skills of the students at SMAN 1 Tuntang English Club at the 2025/2026 academic year. This research using a qualitative descriptive research design and included students of the English Club who were selected through random sampling. Interviews, observation, and documentation were utilized in collecting data for information about students' perceptions and experiences. The data analysis were interpreted according to Miles and Huberman's data condensation, display, and drawing conclusions phases. Findings are that the Starlight Cadre is applied actively and systematically through interactive speaking and listening activities such as storytelling, flashcard games, and pair discussions. Students exhibited noticeable improvement in fluency, pronunciation, vocabulary, and confidence. The observation revealed a positive and supportive learning atmosphere that encouraged participation and communication. The program successfully combined communicative and learner-centered approaches to gain linguistic achievement and motivation. The findings show that well-designed extracurricular activities can potentially enhance students' English speaking ability and confidence in future communication.